FEATURES OF ACCOUNTING FOR BIOLOGICAL ASSETS OF AGRICULTURAL ENTERPRISES OF UKRAINE - Oleh VYSOCHAN; Ihor YAREMKO; Vasyl HYK; Olha VYSOCHAN; Andriy BOYCHUK (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The modern development of the accounting system of agricultural enterprises is under the influence of constant changes, which is justified by the need for further research on theoretical issues of evaluation and accounting of biological assets of agricultural enterprises to make effective management decisions. The article considers the current problems of accounting for the management of biological assets of agricultural enterprises. The study provided an opportunity to establish the composition and classification structure of biological assets, the process of formation of their initial value at the time of receipt and disposal, to determine the features of valuation and accounting in the accounts. The authors use a dialectical and systematic approach, methods of generalization and systematization, analysis and synthesis. An improved method of accounting for current biological assets of animal and crop production using accounts is proposed, which, in contrast to the existing one, will allow detailed accounting of availability and movement by their types and obtain complete accounting information on value for each group. The practical value of research lies in the development of correspondence accounts for the accounting of biological assets, which will allow decisions to be made to improve the efficiency of their management.